ANALISIS GAYA KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA, KOMPENSASI DAN MOTIVASI KERJA DENGAN EMPLOYEE ENGAGEMENT DI BNN KOTA YOGYAKARTA - Wijaya, Benny; Asteria, Beta (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2024)
This study dissects the relationship and impact caused by implementation of transformational leadership, work environment, compensation, and work motivation on employee engagement at the National Narcotics Agency (BNN) of Yogyakarta City. Employee engagement is crucial for enhancing organizational productivity and effectiveness, especially in strategic government agencies like BNN. The study applies quantitative approach with by survey method with the helps of 59 employees of BNN Kota Yogyakarta to fill in the questionnaires that assessed transformational leadership, the work environment, compensation, work motivation, and employee engagement. The analysis was conducted through multiple linear regression. The findings reveal that transformational leadership, compensation, and work motivation have a positive and significant impact on employee engagement, whereas the work environment does not show a significant effect. Transformational leadership was identified as the most influential factor. These results emphasize the critical role of strong leadership, equitable compensation, and high motivation in enhancing employee engagement.